Political leadership analysis - the case of Isabel Díaz Ayuso - Barberá González , Rafael; García, César (Revista Venezolana de Gerencia, 2025)
Political leaders, in Spain and globally, are under constant public scrutiny, both in their daily activities and during election campaigns. This study explores leadership theories—such as trait, behavioral, contingency, and situational theories—as applied to the political sphere. In the methodology section, we highlight key theoretical aspects of perception and leadership. This leads us to analyze the case of Isabel Díaz Ayuso, President of the Community of Madrid. To substantiate these concepts, we examine relevant tools, including electoral surveys and leader evaluation polls. The study’s conclusions address the research questions posed. It is confirmed that one of the primary characteristics of the Madrilenian leader is her credibility, and that her support is based on her authenticity. Furthermore, we determine that, among the various existing leadership types, Ayuso can be classified within contingency models and trait theory. The period analyzed covers the time immediately preceding the last elections in the Community of Madrid, held on May 28, 2023.